A theory of the executive branch : tension and legality - Cohn, Margit (Oxford : Oxford University Press, 2021)
This monograph offers a theoretical foundation of the executive branch in Western democracies and argues that the tension between dominance and submission is maintained by the adoption of various forms of fuzziness, under which a guise of legality masks the absence of the substantive limitation of power.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 9, 2021).
Keywords: Executive power -- Western countries; Executive departments -- Western countries; Separation of powers -- Western countries; Democracy -- Philosophy; Western countries -- Politics and government